Neuroimaging studies in panic disorder [Panik bozukluǧunda beyin görüntüleme çalişmalari] - (:unkn) unknown (My University, 2007)
Objectives and Methods: Panic disorder (PD) is an anxiety disorder that is characterized by repetetive, unpredicted panic attacks in addition to anticipatory anxiety and significant behavioral disturbences related to panic attacks. Brain regions which are related to PD are not adequately idendified. Despite panic attacks are assumed to be related to brainstem, anticipatory anxiety to limbic structures and agoraphobia to frontal cortex, these differentiations are not validated. This article reviews the structural and functional brain imaging studies in PD and discusses the relations between certain neuroanatomic structures and PD. Results: In terms of structural and functional neuroimaging findings, specific consistent differences are reported between PD patients and control subjects. The differences are especially found in parahippocampal areas and frontal cortex. Patients with PD have increased perfusion in right parahippocampal area in respect to left and decreased activity in frontal lobes. Discussion: Decreased activity in prefrontal area is related to increased activity seen in amygdala. Anterior cingulate cortex which is a part of prefrontal cortex is reported to be sensitive to emotional content of sensory input more. Cingulate cortex has an inhibitory effect on amygdala in order to inhibit spontaneous response related to fear and anxiety. The decreased activity in prefrontal cortex that is reported in patients with PD may predispose amygdala for inconvenient activation of structures that are responsible for anxiety symptoms. Right hemisphere is shown to regulate autonomic functions and internal inputs. Increased perfusion in right parahippocampal area in respect to left may be related to the increased sensitivity to internal inputs seen in patients with PD.
Keywords: Amygdala; CT; Frontal cortex; MRI; Neuroimaging; Panic disorder; PET; SPECT